Post Graduate Career Preferences Of Female Medical Students: A Cross Sectional Survey Of 150 Students Of Rawalpindi Medical University - Muneeba Faisal, Arshad Sabir, Zohaib Jamal, Aneeqa Akhtar, Irum Nasir, Muneeba Faisal, Arshad Sabir, Zohaib Jamal, Aneeqa Akhtar, Irum Nasir (Students’ Supplement of Journal of Rawalpindi Medical College, 2022)
Background: Medical field has experienced a constant rise in the induction of female students in medical colleges across the globe. This makes their future career preferences highly significant as they are ultimately going to shape out the fate of various specialties. Keeping in view the prevailing trend of gender distribution in medical colleges of the whole country, it will not be wrong to say that females have become the stake holders of the future of the health care in Pakistan. Thereby, it is the need of the hour to chalk out the future preferences of these female medical students Methods: This is a descriptive cross-sectional study which was done on 150 female medical students of 3rd, 4th and final year MBBS of Rawalpindi Medical University. Data was collected with the help of a questionnaire on which variables such as age, year of study, parents’ occupation, plan and reason of going abroad, plan and reason of studying in Pakistan and preferable field for specialization were entered. Data was analysed by using Statistical Package for Social Sciences (SPSS) version 22.0 respectively are the specialties of choice among female medical students of RMU. Career counselling sessions should be organized and admission policy can be changed to prevent overcrowding of one field and tailor needs of the country. Results: The study showed that among 93.3% of the respondents who were interested in doing postgraduation 61.4% wanted to stay in Pakistan and 38.6% wanted to go abroad. The most frequently opted field of specialty was Medicine (39.3%) followed by Surgery (28%) and Gynaecology and Obstetrics (22%) Conclusion: Our study concluded that medicine, followed by surgery and gynaecology and obstetrics Key words: graduate education, female medical students, career choice